The Effect of Financial Literacy, Security and Accounting Information System Quality on QRIS Usage Decision among MSMEs in Cirebon Regency - Ega Nugraha; Moh Yudi Mahadianto (DINASTI RESEARCH, 2026)
Digital transformation in the payment sector has expanded the use of cashless transactions, yet the continued use of digital payment systems among business actors remains uneven, particularly in regional micro, small, and medium enterprises. This study aims to examine the effects of financial literacy, security, and accounting information system quality on the decision to continue using Quick Response Code Indonesian Standard in business transactions among micro, small, and medium enterprises in Cirebon Regency. This study employed a quantitative explanatory survey with a cross-sectional design. Data were collected from 200 respondents through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling. The results show that financial literacy, security, and accounting information system quality all have positive and significant effects on continued usage decisions. Financial literacy was found to be the strongest predictor, followed by security and accounting information system quality. The model also demonstrated strong explanatory power, indicating that the three variables jointly explained a substantial proportion of the variance in continued usage decisions. These findings suggest that the sustainability of digital payment use among micro, small, and medium enterprises depends on user capability, transaction safety, and system support for financial administration.